The Role of Cognitive Bias in Breast Radiology Diagnostic and Judgment Errors. Issue 4 (29th April 2020) - Loving, Vilert A; Valencia, Elizabeth M; Patel, Bhavika; Johnston, Brian S
Abstract: Cognitive bias is an unavoidable aspect of human decision-making. In breast radiology, these biases contribute to missed or erroneous diagnoses and mistaken judgments. This article introduces breast radiologists to eight cognitive biases commonly encountered in breast radiology: anchoring, availability, commission, confirmation, gambler's fallacy, omission, satisfaction of search, and outcome. In addition to illustrative cases, this article offers suggestions for radiologists to better recognize and counteract these biases at the individual level and at the organizational level.